Non-authorized biographies and the ilegitimacy of fiction - Fachin, Melina Girardi (2016)
This article aims at reflecting about non-authorized biographies. The choice of exploring the topic not only through law but in a dialog with literature opens up new theoretical horizons. The limits of the social subject as well as the limits of the fictional character in a narrative are not always clear in order to define the borders between intimacy and public life. As for Law, a recent trial by the Brazilian Supreme Court, the Direct Action of Unconstitutionality (Ação Direta de Inconstitucionalidade – ADI) 4815, shed more light on the subject, which, nonetheless, is still unconcluded, considering how generic the guarantees of freedom of expression and intimacy defense are in the Brazilian constitutional order. Keeping all that in mind and considering that previous authorization for the publication of biographies is a form of censorship, our intention is to debate the topic considering the density and the new ideas that literature can offer.